Answer: 5.60
Step-by-step explanation: Divide 2.10 by 3. You get 0.7. Then multiply 0.7 by 8 and you get 5.60.
Answer: -3![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
Step-by-step explanation:
-4
+ ![\sqrt{75}](https://tex.z-dn.net/?f=%5Csqrt%7B75%7D)
can be written as
x ![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
which is the same as 2![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
Also ,
can be written as
x
, which is the same as 5![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
Substituting into the main question , we have
-4 (2
) + 5![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
= -8
+ 5![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
= -3![\sqrt{3}](https://tex.z-dn.net/?f=%5Csqrt%7B3%7D)
Answer:
I'm pretty sure it's c but I'm not sure
Answer:
y = (x - 3)² + 6
Step-by-step explanation:
the equation of a parabola in vertex form is
y = a(x - h)² + k
where (h, k ) are the coordinates of the vertex and a is a multiplier
Using the method of completing the square
y = x² - 6x + 15
add/subtract ( half the coefficient of the x- term )² to x² - 6x
y = x² + 2(- 3)x + 9 - 9 + 15
y = (x - 3)² - 9 + 15
y = (x - 3)² + 6 ← in vertex form